The effect of multiwalled carbon nanotube (MWCNT) ratio on electrical properties and electromagnetic shielding effectiveness of PA 6/MWCNT-coated cotton fabrics - USTA, İSMAİL; DEMİREL GÜLTEKİN, NERGİS (TAYLOR & FRANCIS LTD, 2014)
Polyamide 6 (PA 6)/multiwalled carbon nanotube (MWCNT)-coated cotton fabrics having varying amounts of MWCNTs (10, 12, 14 and 16 wt.%) in PA 6 (10, 15 and 20 wt.%) were fabricated with dip coating method to investigate the electromagnetic shielding properties in the frequency range of 15-3000MHz. The effects of MWCNT loading on electrical resistivity, electromagnetic interference shielding effectiveness and also shielding mechanism have been studied. The highest electromagnetic shielding effectiveness value was obtained at 20 wt.% MWCNT loading in 10 wt.% PA 6 and the PA 6/MWCNT-coated composites showed the absoprtion-dominated shielding mechanism.
Keywords: electrical resistivity; polyamide 6; electromagnetic shielding effectiveness (EMSE); multiwalled carbon nanotube; NANOCOMPOSITES